PENGARUH PEMBERIAN PAKAN KOMPLIT DENGAN RASIO JERAMI PADI DAN KONSENTRAT YANG BERBEDA TERHADAP KOMPOSISI KIMIA TUBUH KAMBING BLIGON BETINA - Selvister B. Womakal; Arnol Elyazar Manu; Gusti A. Y. Lestari (Universitas Nusa Cendana, 2014)
The purpose of this study was to determine the effect of complete feed with different ratio of rice straw and concentrate on chemical body composition doe Bligon goat. Animals used in this study is doe Bligon goat as many 12 heads doe with the age range of 8-12 months, the range weight from 7.8 to 18.2 kg (12.2±22.5). The experimental design used was randomized block design with 3 treatments and 4 groups (replicates). Use rations consisting of rice straw and concentrate with the following formula: R1 = 80% rice straw : 20% concentrate; R2 = 70% rice straw : 30% concentrate; R3 = 60% rice straw : 40% concentrate. Measurements the chemical body composition is done on live animals using the